PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), LOAN TO DEPOSIT RATIO (LDR), SUKU BUNGA SBI TERHADAP KINERJAKEUANGAN PERBANKAN (Pada Industri Perbankan Yang Go Public Di Bursa Efek Indonesia Periode Tahun 2014- 2016) - Mohammad Darwis; Agus Widarko; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe purpose of this study is to determine the effect of Capital Adequacy Ratio onFinancial Performance Banking on the Banking Industry Go Public in BEI. To know the effect ofNon Performing Loan on Financial Performance of Banking on Banking Industry Go Public inBEI. To know the influence of Loan to Deposit Ratio on Financial Performance of Banking inBanking Industry Go Public in BEI. To know the effect of SBI Interest Rate on FinancialPerformance of Banking on Banking Industry Go Public in BEI.The type of research used is explanatory. The sample in this study selected as many as 3state banks PT.Bank Rakyat Indonesia Tbk, PT.Bank National Indonesia Tbk, and PT.BankMandiri Tbk. Of the three banks meet all the criteria required by researchers. The 3 year studyperiod from 2014-2016 is taken quarterly. So the sample used is 36 samples with purposivesampling method. Data analysis in this research use multiple linear regression analysis.The result of the research shows that the ratio of Capital Adequacy Ratio has nosignificant positive effect to Financial Performance. Non Performing Loan Ratio has nosignificant positive effect on Financial Performance. Loan To Deposit Ratio ratio has nosignificant negative effect to Financial Performance. The SBI Interest Rate Ratio has aninsignificant negative effect on Financial Performance.Keywords: Capital Adequacy Ratio, Non Performing Loan, Loan To Deposit Ratio, SBI InterestRate and Financial Performance.